PENGARUH METODE BERCERITA DAN POLA ASUH ORANG TUATERHADAP KECERDASAN EMOSIONAL - KARMILA, MILA (JPUD - Jurnal Pendidikan Usia Dini, 2013)
It is important to develop the childrenâ€™s emotional intellegence in the early age since the fact that there are still many children get the troubles in exploring their emotional acts. It occurs because the parents do not guide their children in a right track and teachers use the conventional or traditional method in teaching them in which teachers as the centre of teaching and learning process. Based on that problems, this research is aimed to find out the the influences of telling a story method and parentsâ€™ guidance to childrenâ€™s emotional intellegence. The research desain was a factorial 2x4 experimental study. The technique of sampling was a purposive sampling. The sample was all kindergarten students in grade B at Al â€“ Hidayah and Daarul Qurâ€™an School in South Semarang. There were 20 children taught using a telling a story with a hand puppet and there were 19 children taught using a telling story with a story book. The instruments consisted 30 questions about the parentsâ€™ guidance and 29 questions about a listed observation regarding with emotional intellegence. Technique of data analysis was an two way ANAVA accelerated by hypotesis t-Dunnet. The findings is a telling a story method using a rag doll was more effective in developing the children â€˜s emotional intellegence compared to telling a story using a book with a df value Î±=0,05. Then, the childrenâ€™s emotional intellegence by the parentsâ€™ guidance using authoritative method was much higher compared to the parentsâ€™ using authoritarian, permissive indulgent and permissive indifferent. Finally, the parentsâ€™s guidance using authoritative method really influences significantlly to the level of childrenâ€™s emotional intellegence. Keywords : Emotional Intellegence, Telling a Story Methode, Parenting Style Anak-anak mendapatkan masalah dalam mengeksplorasi tindakan emosional, sehingga kecerdasan emosional anak usia dini perlu dikembangkan. Hal ini terjadi karena orang tua tidak membimbing anak dalam jalur yang benar dan guru menggunakan metode konvensional atau tradisional dalam mengajar dimana guru sebagai pusat pengajaran dan proses belajar. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mengetahui pengaruh metode cerita dan pola asuh orang tua terhadap kecerdasan emosional anak. Desain penelitian adalah 2x4 penelitian eksperimental faktorial. Teknik pengambilan sampel adalah purposive sampling. Sampel adalah semua siswa TK kelas B Al-Hidayah dan Daarul Qur’an School, Semarang selatan. 20 anak diajarkan bercerita dengan boneka tangan dan 19 anak-anak diajarkan bercerita dengan buku cerita. Instrumen penelitian terdiri 30 pertanyaan tentang bimbingan orang tua dan 29 pertanyaan tentang pengamatan mengenai kecerdasan emosional. Teknik analisis data adalah ANAVA dua aarah dipercepat oleh hipotesis t-Dunnet. Hasil penelitian adalah metode cerita menggunakan boneka kain lebih efektif dalam mengembangkan kecerdasan emosional anak dibandingkan dengan bercerita menggunakan buku dengan nilai df Î± = 0,05. Kecerdasan emosional anak yang menggunakan pola asuh otoritatif jauh lebih tinggi dibandingkan dengan orang tua menggunakan pola asuf otoriter, memanjakan permisif dan permisif acuh tak acuh. Akhirnya, bimbingan orang tua dengan menggunakan metode otoritatif sangat berpengaruh signifikan dengan tingkat kecerdasan emosional anak. Kata kunci: Kecerdasan Emosional, Metode Bercerita, pola asuh